Analysis of Dosage Mutation in PARK2 among Korean Patients with Early-Onset or Familial Parkinson's Disease - Chu, Min Kyung (Korean Neurological Association, 2014)
BACKGROUND AND PURPOSE: There is some controversy regarding heterozygous mutations of the gene encoding parkin (PARK2) as risk factors for Parkinson's disease (PD), and all previous studies have been performed in non-Asian populations. Dosage mutation of PARK2, rather than a point mutation or small insertion/deletion mutation, was reported to be a risk factor for familial PD; dosage mutation of PARK2 is common in Asian populations. METHODS: We performed a gene-dosage analysis of PARK2 using real-time polymerase chain reaction for 189 patients with early-onset PD or familial PD, and 191 control individuals. In the case of PD patients with heterozygous gene-dosage mutation, we performed a sequencing analysis to exclude compound heterozygous mutations. The association between heterozygous mutation of PARK2 and PD was tested. RESULTS: We identified 22 PD patients with PARK2 mutations (11.6%). Five patients (2.6%) had compound heterozygous mutations, and 13 patients (6.9%) had a heterozygous mutation. The phase could not be determined in one patient. Three small sequence variations were found in 30 mutated alleles (10.0%). Gene-dosage mutation accounted for 90% of all of the mutations found. The frequency of a heterozygous PARK2 gene-dosage mutation was higher in PD patients than in the controls. CONCLUSIONS: Heterozygous gene-dosage mutation of PARK2 is a genetic risk factor for patients with early-onset or familial PD in Koreans.